Choice between helping vs not helping: level of mastery in the task - Carpio, Claudio (2019)
Studies carried out to identify conditions that promote altruism have suggested that factors such as situational consequences and the introduction of verbal components in a task probabilize the individuals' choice to work under shared contingencies. However, it has been found that the presence of these variables is not enough to guarantee that individuals help. It has been considered that the behavioral capacity to perform effectively in a task (i.e. domain level) is a dispositional variable that can facilitate or impede the choice of individuals to work under shared contingencies. Based on this, the objective of this work consisted of evaluating the effects of different levels of domain in an arithmetic task (high and low) on the choice of helping / not helping a partner to perform arithmetic operations. The task was to perform different types of arithmetic operations (addition, subtraction, multiplication and division) to obtain points. Once they accumulated 20 points, participants were presented with the option to choose between helping a partner to solve operations or continue with their task. The results show that participants with high arithmetic domain chose to help their partner more frequently than the participants with low arithmetic domain (40% vs. 23%, respectively). The importance of the task domain level as a dispositional factor in the choice between helping or not helping is discussed.